Efficacy of highly active antiretroviral therapy in HIV-infected children participating in Thailand's National Access to Antiretroviral Program - Thanyawee Puthanakit (2018)
Background. Programs for access to antiretroviral treatment were only recently implemented in developing countries. This study aimed to describe the effect of highly active antiretroviral therapy (HAART) in treating human immunodeficiency virus (HIV)-infected children in Thailand's National Access to Antiretroviral Program for People Living with HIV/AIDS. Methods. From August 2002 to July 2003, a total of 107 children were enrolled in the study. They received HAART consisting of either nevirapine or efavirenz, together with lamivudine and stavudine. Generic drugs and/ or adult formulations were used. CD4 lymphocyte count, plasma HIV RNA level, and weight-for-age and height-for-age z scores were measured before, 2 months after, and every 6 months after initiation of HAART. A genotypic resistance assay was performed for patients with poor virological response. Results. The mean age of the patients was 7.7 years (range, 2.1-13.8 years). At baseline, the median CD4 cell percentage was 3%, and the plasma HIV RNA level was 5.4 log10copies/mL. Four patients died from HIV-related illness. After 72 weeks of HAART, the median CD4 cell percentage was 21%, and 76% of patients had HIV RNA levels of <50 copies/mL. The mean weight-for-age and height-for-age z scores increased from -1.9 to -1.3 (P < .0001) and from -2.3 to -2.0 (P<.0001), respectively. The percentage of patients who took &95% of prescribed medications during the interval between every follow-up visit was 86% For patients with suboptimal virological response, the most common resistance mutations among HIV isolates were associated with lamivudine and with nonnucleoside reverse-transcriptase inhibitors. Conclusion. In this resource-limited setting, HAART is safe and effective for HIV-infected children despite initiation of treatment during the advanced stage of disease. The use of generic and nonpediatric drug formulations is feasible. © 2005 by the Infectious Diseases Society of America. All rights reserved.